Influence of temperature on the growth of fecal coliform (Stamford Journal of Microbiology, 2017)
The cellular response against environmental stresses is one of the most highly conserved regulatory features among all organisms. The exposure of cells to stresses such as heat shock leads to the accumulation of partially and fully denatured proteins that interfere with normal cellular function. Present study was designed to examine the growth and physiology of Escherichia coli at different temperatures in our laboratory condition. With a previous observation of Escherichia coli growth cessation by the increase in temperature on different culture media, current study further extended the examination of the influence of temperature on the growth behavior of fecal coliform on minimal media, a slight retardation in the colony and cell morphology was noticed for fecal coliform at 47 °C within 36 hours to 72 hours of incubation. Consistent result was also found in spot test for fecal species at 45°C.Stamford Journal of Microbiology, Vol.6(1) 2016: 20-23